2022
DOI: 10.3390/jcm11236955
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Free Anesthesia in Thoracic Surgery: A Systematic Review and Meta Analysis

Abstract: Introduction: Recent studies showed that balanced opioid-free anesthesia is feasible and desirable in several surgical settings. However, in thoracic surgery, scientific evidence is still lacking. Thus, we conducted the first systematic review and meta-analysis of opioid-free anesthesia in this field. Methods: The primary outcome was the occurrence of any complication. Secondary outcomes were the length of hospital stay, recovery room length of stay, postoperative pain at 24 and 48 h, and morphine equivalent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
1
2
0
2
Order By: Relevance
“…No significant differences were observed in NRS scores and rescue analgesia rates between the two groups at the same time after surgery. The pain scores were consistent with a recent meta-analysis by D'Amico that found no difference in pain scores between OFA and OA at 24 h after thoracic surgery (MD -1.69 [-3.82,0.43]; P = 0.12) (28). The NRS was the highest at 6 h after surgery due to the weakening of the analgesic effect of the intercostal nerve block and the stimulation of the pleura by the thoracic drainage tube.…”
Section: Discussionsupporting
confidence: 90%
“…No significant differences were observed in NRS scores and rescue analgesia rates between the two groups at the same time after surgery. The pain scores were consistent with a recent meta-analysis by D'Amico that found no difference in pain scores between OFA and OA at 24 h after thoracic surgery (MD -1.69 [-3.82,0.43]; P = 0.12) (28). The NRS was the highest at 6 h after surgery due to the weakening of the analgesic effect of the intercostal nerve block and the stimulation of the pleura by the thoracic drainage tube.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the use of opioid drugs, the existing studies demonstrate contradictory evidence [24,25] .…”
Section: Discussionmentioning
confidence: 99%
“…By using a multimodal nonopioid approach to anesthesia and perioperative analgesia, patients are able to avoid opioids altogether with either similar or improved outcomes compared to standard opioid analgesia [ 30 32 ]. A meta-analysis by D’Amico and colleagues examined the use of OFA in thoracic surgery and concluded that it was associated with lower rates of complications, lower pain scales and lower morphine consumption postoperatively [ 33 ]. While it remains to be seen how this could be utilized in patients with chronic opioid use and OUD, its effectiveness in decreasing perioperative opioid use may be an important method of harm reduction in the future.…”
Section: Discussionmentioning
confidence: 99%